SiC and B₄C as electrocatalyst support materials for low temperature fuel cells - Jackson, Colleen (Centre for Catalysis Research, 2018)
Supported nano-catalyst technologies are key for increasing the catalyst utilisation and achieving economically feasible platinum metal loadings in hydrogen polymer electrolyte fuel cells (PEFCs). High surface area carbons are commonly utilised as support materials for platinum due to low cost, large surface areas and high conductivity. However, PEFCs using this technology undergo oxidation of carbon supports, significantly reducing the lifetime of the fuel cell. In this work, silicon carbide and boron carbide are investigated as alternative catalyst support materials to carbon, for the oxygen reduction reaction for low temperature fuel cells. Electrochemical testing, accelerated degradation studies as well as advanced characterisation techniques were used to clarify the structure-property relationships between catalyst morphology, metal-support interaction, ORR activity and surface adsorption onto the Pt nanoparticles. Extended X-ray Absorption Fine Structure (EXAFS) analysis gave insights into the shape of the clustered nanoparticles while X-ray Photoelectron Spectroscopy (XPS) and in-situ X-ray Absorption Near-Edge Spectroscopy (XANES) analysis provided information into how the metal-support interaction influences surface adsorption of intermediate species. Electronic metal-support interactions between platinum and the carbide supports were observed which influenced the electrochemical characteristics of the catalyst, in some cases increasing the oxygen reduction reaction activity, hydrogen oxidation reaction activity and Pt stability on the surface of the support.